2014
DOI: 10.15653/tpg-131130
|View full text |Cite
|
Sign up to set email alerts
|

Field study on swine influenza virus (SIV) infection in weaner pigs and sows

Abstract: SummaryObjective: The aim of this field study was to explore the occurrence of and factors associated with the detection of swine influenza virus (SIV) by RTqPCR in weaner pigs and sows from herds with a history of respiratory or reproductive disorders. Material and methods: The sample set was based on nasal swabs from 823 sows (123 submissions) and 562 weaner pigs (80 submissions). Nasal swab samples were taken and submitted by 51 veterinary practices from all over Germany. Corresponding to the pig density mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…Therefore new gilts and piglets may represent the most epidemiologically significant reservoirs for IAVs in swine breeding herds. Sows were not included in our study because they have been found to have a low probability of influenza positivity in endemically affected herds [15, 19, 20]. Our results also indicate that there was a strong association between IAV infection and annual quarter and that this association was still statistically significant after controlling for the subpopulation effect.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Therefore new gilts and piglets may represent the most epidemiologically significant reservoirs for IAVs in swine breeding herds. Sows were not included in our study because they have been found to have a low probability of influenza positivity in endemically affected herds [15, 19, 20]. Our results also indicate that there was a strong association between IAV infection and annual quarter and that this association was still statistically significant after controlling for the subpopulation effect.…”
Section: Discussionmentioning
confidence: 63%
“…At each visit, three pig subpopulations were sampled: a) replacement females, resident on-farm for less than 4 weeks (new gilts), b) replacement females, resident on-farm for more than 4 weeks (gilts), and c) neonatal pigs less than 21 days of age (piglets). Adult animals (sows) were not included since prior studies consistently reported a low probability of influenza detection in this subpopulation [15, 19, 20]. Due to schedules for delivery of replacement females, eligible populations of new gilts were only present at 21 of the 60 sampling events.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent of the subtype, the disease can emerge both in a subclinical and in an acute way, with varying severity, showing febrile illness together with respiratory disease [4,8,11]. An involvement in reproductive disorders, such as return to oestrus, abortion or small litters, is assumed, although a causal link could not be shown in all studies [12,13]. Numerous case reports as well as a case-control study on a naive Norwegian pig subpopulation describe the emergence of reproductive disorders in context with the infection with influenza A virus [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Der in Schweinepopulationen häufig endemisch vorliegende Subtyp H1 av N1 wurde Ende der 1970er Jahre von wildlebenden Wasservögeln auf Schweine übertragen und infiziert seitdem viele Schweinebetriebe endemisch (35). In Deutschland untersuchten Meiners et al (22) annähernd 600 Nasentupfer von Absetzferkeln mit Atemwegserkrankungen aus dem gesamten Bundesgebiet und konnten bei insgesamt 54% der Tiere FLUAVsw nachweisen. Bei 60,5% der Isolate handelte es sich um H1 av N1, bei jeweils 14% um H1N2 und H3N2 sowie bei 11,5% um H1N1pdm.…”
Section: Introductionunclassified